Digital Media in Religious Education : Challenges and Opportunities - Anggun Wida Prawira; Aurida Mahelvi; Bilqis Mufidah (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
With the rise of digital media, religious education faces new challenges and opportunities. This article investigates the integration of digital tools in teaching religious studies, focusing on their potential to make learning more engaging and accessible. The study analyzes both the benefits, such as interactivity and inclusivity, and the risks, including misinformation and digital distractions. Practical recommendations are provided for educators to effectively leverage digital platforms while maintaining the integrity of religious teachings.